CORAL ROCK ASH AS A SUPPLEMENTARY FILLER IN ASPHALT CONCRETE WEARING COURSE: LABORATORY PERFORMANCE AND MECHANISTIC–EMPIRICAL SERVICE-LIFE PREDICTION - Miftahulkhair, Muh; Wicaksono, Achmad; Reza Hasrul, Muhammad; Katjo, Syukuriah; Sainuddin; Alwi, Almayana; Nofianti Idris, Risma (Journal of Applied Engineering Science, 2026)
Flexible pavements with hot-mix asphalt (HMA) may underperform when conventional mineral filler provides insufficient mastic stiffness and moisture resistance. This study evaluates coral rock ash (CRA) as a partial replacement of conventional mineral filler in an asphalt concrete wearing course (AC–WC) mixture to improve laboratory performance and predicted service life. CRA was introduced at 0–10% of the total mixture mass, replacing an equivalent portion of filler in the gradation. Marshall stability/flow and indirect tensile strength (ITS, tensile strength) were measured at an optimum asphalt content of 6%. To link mixture-scale changes to structural performance, layer responses were computed using KENPAVE multilayer elastic analysis, where the HMA elastic modulus was derived from the ITS-based stiffness correlation used in the study (with Poisson’s ratio held constant), enabling mechanistic–empirical estimation of critical strains and allowable load repetitions. Regression analysis identified 4.8% CRA as optimal, yielding peak Marshall stability (1060.7 kg) and the smallest 7-day strength loss after 60 °C conditioning. Relative to the control, ITS increased by 22.6% (11.62→14.25, unit-consistent with the original dataset). In the mechanistic analysis, the improved mixture stiffness led to a reduction in bottom-HMA tensile strain (εt) and a corresponding increase in predicted allowable repetitions, extending the design life of the reference pavement section from 5 to 7 years. These findings indicate that CRA is a feasible, locally available supplementary filler for improving HMA performance and extending service life in coastal regions, provided that sourcing uses non-living, naturally stranded coral debris and complies with environmental regulations.
Keywords: hot-mix asphalt, coral rock ash, multilayer elastic analysis, mechanistic–empirical design, pavement service life